One-Year Outcomes After Transcatheter Insertion of an Interatrial Shunt Device for the Management of Heart Failure With Preserved Ejection Fraction. (December 2016) - Kaye, David M.; Hasenfuß, Gerd; Neuzil, Petr; Post, Martijn C.; Doughty, Robert; Trochu, Jean-Noël; Kolodziej, Adam; Westenfeld, Ralf; Penicka, Martin; Rosenberg, Mark; Walton, Antony; Muller, David; et al.
Abstract : Background—: Heart failure with preserved ejection fraction has a complex pathophysiology and remains a therapeutic challenge. Elevated left atrial pressure, particularly during exercise, is a key contributor to morbidity and mortality. Preliminary analyses have demonstrated that a novel interatrial septal shunt device that allows shunting to reduce the left atrial pressure provides clinical and hemodynamic benefit at 6 months. Given the chronicity of heart failure with preserved ejection fraction, evidence of longer-term benefit is required. Methods and Results—: Patients (n=64) with left ventricular ejection fraction ≥40%, New York Heart Association class II–IV, elevated pulmonary capillary wedge pressure (≥15 mm Hg at rest or ≥25 mm Hg during supine bicycle exercise) participated in the open-label study of the interatrial septal shunt device. One year after interatrial septal shunt device implantation, there were sustained improvements in New York Heart Association class ( P <0.001), quality of life (Minnesota Living with Heart Failure score, P <0.001), and 6-minute walk distance ( P <0.01). Echocardiography showed a small, stable reduction in left ventricular end-diastolic volume index ( P <0.001), with a concomitant small stable increase in the right ventricular end-diastolic volume index ( P <0.001). Invasive hemodynamic studies performed in a subset of patients demonstrated a sustained reduction in the workload corrected exercise pulmonary capillary wedge pressure ( P <0.01). Survival at 1 year was 95%, and there was no evidence of device-related complications. Conclusions—: These results provide evidence of safety and sustained clinical benefit in heart failure with preserved ejection fraction patients 1 year after interatrial septal shunt device implantation. Randomized, blinded studies are underway to confirm these observations. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01913613. Abstract : Supplemental Digital Content is available in the text.